2019
DOI: 10.1186/s12870-019-2165-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of agronomic traits in bread wheat reveals novel putative alleles for future breeding programs

Abstract: BackgroundIdentification of loci for agronomic traits and characterization of their genetic architecture are crucial in marker-assisted selection (MAS). Genome-wide association studies (GWAS) have increasingly been used as potent tools in identifying marker-trait associations (MTAs). The introduction of new adaptive alleles in the diverse genetic backgrounds may help to improve grain yield of old or newly developed varieties of wheat to balance supply and demand throughout the world. Landraces collected from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 65 publications
20
69
1
Order By: Relevance
“…The significance of each SSR marker for studied traits was assessed using a two-tailed t-test (Lüders et al, 2016;Rahimi et al, 2019). The results of the test suggested that five out of seven SSRs were significant at least for one studied trait (see Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of each SSR marker for studied traits was assessed using a two-tailed t-test (Lüders et al, 2016;Rahimi et al, 2019). The results of the test suggested that five out of seven SSRs were significant at least for one studied trait (see Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Downstream applications included functional genetic studies for drought tolerance and GWAS applications, which in turn can feed into marker-assisted breeding efforts. In a different application, chlorophyll fluorescence and thermal (infrared) phenotyping of ~300 Iranian wheat cultivars combined with GWAS revealed adaptive alleles for drought stress useful for marker-assisted selection [91] .…”
Section: Introductionmentioning
confidence: 99%
“…The Persian farmers irrigate their farms two to four more times with the stored water after spike appearance to avoid yield loss due to late-season drought stress. This strategy leads to a significant increase in wheat grain yield [ 27 ]. The impact of drought stress and irrigation at the end of the growing season on different genotypes needs further investigations.…”
Section: Introductionmentioning
confidence: 99%